The Correlation of Cognitive and Functional Ability among Elderly - Gede Budhi Artha Yoga; I.A Pascha Paramurthi; I Putu Astrawan (Physical Therapy Journal of Indonesia, 2021)
Background: Elderly is someone who has reached the age of 60 years and over. Increasing age will experience changes in the structure and physiology of the brain, which will affect cerebral blood flow and metabolism, which will affect the decline in cognitive function. The cognitive impairment will have a negative impact on the process of thinking, remembering, and processing information. Objective: To determine the relationship between cognitive and functional abilities in the elderly. Methods: A cross-sectional study was conducted on April 2021 with a population of elderly who met the inclusion and exclusion criteria. The elderly selected by purposive sampling obtained 52 samples. Cognitive measurement using MMSE and functional ability with IADL Lawton. Data were analyzed using a computer's Somers' d test to determine the relationship between cognitive and functional abilities. Results: Analysis of the relationship between cognitive and functional abilities of 52 elderly using Somers'd showed a p-value of 0.001 (p<0.005) which reported a significant relationship between cognitive and functional abilities. Conclusion: there was a relationship between cognitive and functional abilities in the elderly.